Immune-Modified Response Evaluation Criteria In Solid Tumors (imRECIST): Refining Guidelines to Assess the Clinical Benefit of Cancer Immunotherapy - Hodi, F Stephen; Ballinger, Marcus; Lyons, Benjamin; Soria, Jean-Charles; Nishino, Mizuki; Tabernero, Josep; Powles, Thomas; Smith, David; Hoos, Axel; McKenna, Chris; Beyer, Ulrich; Rhee, Ina; et al. (Journal of clinical oncology, 2018)
Purpose Treating solid tumors with cancer immunotherapy (CIT) can result in unconventional responses and overall survival (OS) benefits that are not adequately captured by Response Evaluation Criteria In Solid Tumors (RECIST) v1.1. We describe immune-modified RECIST (imRECIST) criteria, designed to better capture CIT responses. Patients and Methods Atezolizumab data from clinical trials in non-small-cell lung cancer, metastatic urothelial carcinoma, renal cell carcinoma, and melanoma were evaluated. Modifications to imRECIST versus RECIST v1.1 included allowance for best overall response after progressive disease (PD) and changes in PD definitions per new lesions (NLs) and nontarget lesions. imRECIST progression-free survival (PFS) did not count initial PD as an event if the subsequent scan showed disease control. OS was evaluated using conditional landmarks in patients whose PFS differed by imRECIST versus RECIST v1.1. Results The best overall response was 1% to 2% greater, the disease control rate was 8% to 13% greater, and the median PFS was 0.5 to 1.5 months longer per imRECIST versus RECIST v1.1. Extension of imRECIST PFS versus RECIST v1.1 PFS was associated with longer or similar OS. Patterns of progression analysis revealed that patients who developed NLs without target lesion (TL) progression had a similar or shorter OS compared with patients with RECIST v1.1 TL progression. Patients infrequently experienced a spike pattern (TLs increase, then decrease) but had longer OS than patients without TL reversion. Conclusion Evaluation of PFS and patterns of response and progression revealed that allowance for TL reversion from PD per imRECIST may better identify patients with OS benefit. Progression defined by the isolated appearance of NLs, however, is not associated with longer OS. These results may inform additional modifications to radiographic criteria (including imRECIST) to better reflect efficacy with CIT agents.